2018
DOI: 10.1164/rccm.201709-1835oc
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial and Smooth Muscle Cell Interaction via FoxM1 Signaling Mediates Vascular Remodeling and Pulmonary Hypertension

Abstract: Multiple factors derived from dysfunctional ECs induced FoxM1 expression in SMCs and activated FoxM1-dependent SMC proliferation, which contributes to pulmonary vascular remodeling and PH. Thus, targeting FoxM1 signaling represents a novel strategy for treatment of idiopathic PAH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
143
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(167 citation statements)
references
References 54 publications
13
143
3
Order By: Relevance
“…A previous study has also revealed that PI3Kα signaling via PDK1/AKT could mediate FGF2-induced FOXM1 upregulation in lung fibroblasts (32). Furthermore, FOXM1 signaling mediated vascular remodeling and pulmonary hypertension, as previously reported (27). Collectively, these studies indicated that PI3K/AKT and MEK/ERK pathways and FOXM1 may serve as potential post-receptor signaling pathways that mediate the profibrotic effect of CXCL12 in lung fibroblasts.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…A previous study has also revealed that PI3Kα signaling via PDK1/AKT could mediate FGF2-induced FOXM1 upregulation in lung fibroblasts (32). Furthermore, FOXM1 signaling mediated vascular remodeling and pulmonary hypertension, as previously reported (27). Collectively, these studies indicated that PI3K/AKT and MEK/ERK pathways and FOXM1 may serve as potential post-receptor signaling pathways that mediate the profibrotic effect of CXCL12 in lung fibroblasts.…”
Section: Discussionsupporting
confidence: 72%
“…Multiple cell types can express CXCR4/CXCL12 in lung tissues (especially in fibrotic lungs), including fibroblasts, epithelial cells, vascular endothelial cells and some inflammatory cells (26)(27)(28)(29). As previously reported, a major population of CXCR4+ cells was localized close to the fibroblastic foci in lung tissue sections from patients with IPF (28,29).…”
Section: Discussionsupporting
confidence: 65%
“…; Dai et al . ). PH development is often associated with early and persistent perivascular inflammation in animal models of PH (Li et al .…”
Section: Introductionmentioning
confidence: 97%
“…Findings from studies have "caught up" with this approach. With promising strategies under investigation to interrupt the proliferative, neoplastic-like nature of the disease, 1,22 patients and PAH care providers can hope to see continued improvement in outcome, perhaps hopedfor eradication of this disease.…”
Section: Summary and Thoughtsmentioning
confidence: 99%